A Case of Fatal Necrotizing Fasciitis Arising From Chronic Lymphedema. (December 2013) - Jun, Young Joon; Kang, In Sook; Lee, Jung Ho; Kim, Sue Min; Kim, Young Jin
Chronic lymphedema and lymphangitis are common adverse effects following treatment for gynecological cancer. Because the early symptoms of necrotizing fasciitis are similar to those of lymphangitis, fatal outcome can occur if patients or physicians underestimate this condition. Here, we present a case of necrotizing fasciitis in a patient with chronic lymphedema.